Magnetorheology of core–shell typed dual-coated carbonyl iron particle fabricated by a sol–gel and self-assembly process. (September 2015) - Liu, Ying Dan; Choi, Hyoung Jin
Graphical abstract: Highlights: A self-assembly method is applied to prepare dual-coated carbonyl iron particles. The first layer of silica on CI particle is introduced using sol–gel method. The dual-coated particles show reduced but still good solid-like modulus. Relaxation modulus of is obtained via data conversion by using Schwarzl equation. Yield stresses of the MR fluid are fitted by a universal equation. Abstract: Micron-sized soft-magnetic carbonyl iron (CI) particles, which are the most widely applied magnetic particles in magnetorheological (MR) fluids, were evaluated as a candidate for modification by coating to reduce their density and provide rich surface properties. Both silica and multi-walled carbon nanotubes (MWNTs) dual-coated soft-magnetic CI particles were fabricated and applied as magneto-responsive solid particles in an MR fluid. The silane-grafted CI microspheres were coated with the first layer of silica using a sol–gel method, and the second layer of MWNTs was then wrapped using a layer-by-layer process in both positive and negative polyelectrolytes. The rheological properties from the dynamic and steady shear tests of the MR fluid when dispersed in silicone oil were examined using a rotational rheometer under an applied magnetic field. The Schwarzl equation was also used to determine relaxation modulus of the MR fluid, based on the dynamic moduli measured from a frequency sweep method.